Implementation of Individual Educational Trajectories in University - O. E. Iatsevich; N. I. Speranskaya; N. V. Omelaenko; V. V. Iudashkina; L. N. Shabatura (Высшее образование в России)
The significance of the study is determined by the fact that education receives a new round in its development. It is specified by modern trends in the digital world economy, which makes special demands on the human capital development, where higher education institutions play a leading role. The education models using individual educational trajectories are considered one of the most promising at the present stage of society formation, as evidenced by the message of the President of the Russian Federation V.V. Putin and the introduction of a number of amendments to the law on education of the Russian Federation.The purpose of the study presented by the authors is to describe, analyze and summarize pedagogical  experience  of  IET  implementation  in  higher  educational  institutions.  The  authors  chose  general and  scientific  methods  as  a  methodological  basis:  phenomenological,  sociometric  methods  included pedagogical observation, retrospective and statistical analysis and synthesis. Empirical data are based on the survey result of the 1st, 2nd and 3rd years students (n=117). In spite of the fact that individual educational trajectories are a pedagogical phenomenon, the study can be classified as interdisciplinary, it involves such sciences as psychology, philosophy, and sociology. The IET realization has a number of advantages, at the same time IET is not free from some disadvantages. The problems identified in the course of the study in the implementation of IOT can be minimized, taking into account the recommendations proposed by the authors of the article, which will rationalize and humanize the education-al process. The scientific novelty and practical significance lies in the theoretical and practical significance of the conducted research, which helps understand the IET content and essence in pedagogical practice. The generalized empirical experience can serve a basis for the development of special courses, textbooks, teaching materials and recommendations on the organization of IET in higher education.